Employment, growth and development : essays on a changing world economy - Nayyar, Deepak (Abingdon, Oxon : Routledge, 2017)
This book examines the critical themes of employment, growth and development, to focus on challenges and opportunities, both old and new, in the contemporary world economy. The essential theme that runs through the book is that there is a strong relationship not only between employment and growth but also between employment and development, where the causation runs in both directions. The author shows how employment transforms economic growth into meaningful development by providing livelihoods and incomes to people. While the book is primarily concerned with developing countries, it considers industrialized countries as points of reference or comparison, since the latter are a large part of an interdependent world, in which problems faced by the two sets of countries are frequently connected and sometimes common. The ten essays in this volume also provide a macroeconomic analysis of development problems situated in the wider context of a changing world economy, exploring possible solutions, to understand the implications for countries and for people.
Keywords: Labor market